Cistanoside F Ameliorates Lipid Accumulation and Enhances Myogenic Differentiation via AMPK-Dependent Signaling in C2C12 Myotubes - Meng-Ling Ma; Ze-Ling Tang; Li-Ping Chen; Xiang-Nan Qin; Ke-Fei Xiao; Wei-Liang Zhu; Yong Zhang; Zhang-Bin Gong (Cells, 2025)
Sarcopenic obesity (SO) is a metabolic disorder for which no effective pharmacological treatments are currently available. Cistanoside F (Cis), a phenoxyethanol-derived compound, remains relatively unexplored in the context of lipid metabolism regulation, as well as its potential mechanisms and therapeutic applications in metabolic disorders. Consequently, this study aimed to evaluate the potential of Cis in ameliorating the pathological manifestations of SO in C2C12 cells. Two classical adipogenic differentiation models using C2C12 cells were employed to quantitatively assess the ability of Cis to inhibit lipid droplet formation, utilizing Oil Red O staining coupled with high-content imaging analysis. Markers associated with adipogenic and myogenic differentiation were examined using quantitative real-time PCR and Western blotting. Our experimental findings demonstrated that Cis significantly attenuated lipid droplet accumulation and promoted muscle protein synthesis via the modulation of PPARγ, ATGL, CPT1b, and UCP1 expression during lipogenic differentiation of C2C12 cells. Cis significantly upregulated the phosphorylation and expression levels of key metabolic regulators, including p-AMPK/AMPK, p-ACC1/ACC1, and MHC. We identified a positive regulatory feedback mechanism between AMPK signaling and MHC expression in the adipogenic differentiation model, suggesting that Cis exerts its therapeutic effects through AMPK-dependent pathways. This is the first study to provide the first experimental evidence supporting the therapeutic potential of Cis for metabolic regulation, targeting adiposity reduction and muscle mass enhancement. Furthermore, Cis exhibited potent anti-inflammatory properties, as demonstrated by its ability to significantly downregulate proinflammatory mediators, including IL-6 and p-NF-κB/NF-κB, during adipogenic differentiation. These novel findings regarding the anti-inflammatory mechanisms of Cis will form the basis for our subsequent in-depth mechanistic investigations.